IMPLEMENTASI PEMBELAJARAN BERBASIS TECHNOLOGICAL PEDAGOGIGAL CONTENT KNOWLEDGE (TPACK) DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS 2 SD NEGERI INPRES MALOMPO, NABIRE - Etni Malisan, Arsyati; Danu Rusmawati, Retno; Wiyarno, Yoso (Universitas Negeri Medan, 2025)
Abstract: Abstract This study aims to analyze the effect of the Technological Pedagogical Content Knowledge (TPACK) -based learning model and direct instruction on the mathematics learning outcomes of second-grade elementary students, with learning motivation considered as a moderating variable. A quasi-experimental approach with a 2x2 factorial design was employed, involving 80 students from SD Negeri Inpres Malopo, Nabire. The research instruments included a mathematics achievement test and a learning motivation questionnaire, both of which were validated for reliability and construct validity. Data were analyzed using two-way ANOVA after meeting the assumptions of normality and homogeneity. The results indicate that the TPACK-based learning model is significantly more effective than direct instruction in improving students' mathematics learning outcomes (p < 0.05). Furthermore, learning motivation has a significant impact on learning achievement; students with high motivation achieved better outcomes than those with low motivation. A significant interaction effect was also found between the learning model and motivation level (p < 0.05), where highly motivated students who received TPACK-based instruction obtained the highest scores. These findings highlight the importance of combining innovative pedagogical approaches and strategies to enhance student motivation in order to improve mathematics education quality at the elementary level. Keyword: TPACK, learning motivation, learning outcomes, mathematics education, elementary school Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran berbasis Technological Pedagogical Content Knowledge (TPACK) dan pembelajaran langsung terhadap hasil belajar matematika siswa kelas 2 SD, dengan mempertimbangkan motivasi belajar sebagai variabel moderator. Penelitian ini menggunakan pendekatan kuasi eksperimen dengan desain faktorial 2x2 yang melibatkan 80 siswa di SD Negeri Inpres Malopo, Nabire. Instrumen penelitian terdiri atas tes hasil belajar dan angket motivasi belajar yang telah diuji validitas dan reliabilitasnya. Analisis data dilakukan melalui uji ANAVA dua jalur setelah memenuhi prasyarat normalitas dan homogenitas. Hasil penelitian menunjukkan bahwa model pembelajaran TPACK secara signifikan lebih efektif dibandingkan pembelajaran langsung dalam meningkatkan hasil belajar matematika siswa (p < 0,05). Selain itu, motivasi belajar berpengaruh signifikan terhadap hasil belajar; siswa dengan motivasi tinggi memperoleh capaian akademik yang lebih tinggi dibandingkan siswa bermotivasi rendah. Temuan lainnya menunjukkan adanya interaksi yang signifikan antara model pembelajaran dan tingkat motivasi belajar (p < 0,05), di mana siswa bermotivasi tinggi yang mengikuti pembelajaran berbasis TPACK menunjukkan hasil belajar tertinggi. Temuan ini menegaskan pentingnya integrasi pendekatan pedagogis inovatif dan strategi peningkatan motivasi belajar dalam rangka meningkatkan kualitas pembelajaran matematika di sekolah dasar. Kata Kunci: TPACK, motivasi belajar, hasil belajar, pembelajaran matematika, sekolah dasar